Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 192630994 species occurrences available in GBIF matching the query: { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Fossil", "BasisOfRecord is Unknown evidence" ] } The dataset includes 192630994 records from 14404 constituent datasets: 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 1 records from Riedkanal Bötzingen. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 11961 records from MEXU/Leguminosae. 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 2 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 331 records from (Table IIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of the Ben Gurion Section, Israel. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 11 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 50873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 12 records from A Catalogue and Historical Study of the Odonata of Ecuador. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 25 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 27 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1054 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 14 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 254 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 5000 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 4 records from Knechtweide (Kohlfurth). 322 records from Collections ichtyologiques et herpétologiques (BOUM). 1584 records from MCP-Mamiferos - Coleção de Mamíferos. 236 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 65903 records from Norwegian Lepidoptera working group. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 14 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 1 records from Archaeomalthus - (Coleoptera, Archostemata) a ‘ ghost adult ’ of Micromalthidae from Upper Permian deposits of Siberia?. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 973 records from Zambian Bat Collections Worldwide. 28 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 8 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 466 records from PSU-Seagrass Collection. 1014 records from Pollen profile ADR353. 270 records from bmhs_weatherheadshell_collection. 1196 records from Entomological collection of the National Museum. 30917 records from Vascular plants of south-central China. 205 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 1 records from Sächsische Schweiz (Pfaffenstein). 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1 records from Miriapodi di alcune grotte della Campania. 554 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 4 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 5 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 22 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 881 records from Helmintos parásitos de peces del sureste de México. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 11 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 416 records from Radiolaria assemblage in sediment core GIK23259-2. 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 26 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 4 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 26111 records from University of California Santa Barbara Invertebrate Zoology Collection. 748 records from (App 10) Relative contents of indicator species of planktonic foraminifera in sediments from Core S-17666. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 63507 records from Entomology Collection at the Natural History Museum of Utah. 3 records from Three new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 1 records from Schulman's Neotropical Adelobotrys database. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 6 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 365 records from Colección Herpetológica de la Patagonia. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 116480 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3184 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 1 records from Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil. 38 records from Comparative morphology and taxonomy of the tiger moth genus Epanycles Butler (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina), with notes on related genera. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 105857 records from Fish specimens of Kagoshima University Museum. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13647 records from UTEP Invertebrates (Arctos). 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 998 records from Korean Ethnobotany Database. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 23643 records from CNIN/Abejas de México/Apoidea. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 3 records from The Mastigitae genus † Baltostigus in Upper Eocene Rovno amber (Coleoptera: Staphylinidae: Scydmaeninae). 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 30008 records from Lepidoptera specimen database of Japan. 143811 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 33 records from Smear slide analysis on sediment core GeoB4214-1. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 29019 records from Collection Vermes - ZMB. 783930 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 7 records from Parasitoides de Cochinilla. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 45 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Description of a new genus and two new species of Forsteriini Tippmann, 1960 from Peru (Coleoptera, Cerambycidae, Lamiinae). 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 67 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 371 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 66 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 31 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1513 records from M. Gollop Collection. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53207 records from Naturalis Biodiversity Center (NL) - Diptera. 37 records from FBIP: scallop population genetics. 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 2789 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 2 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Berlese's Primitive Oribatid Mites. 2 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 686 records from Nannofossil abundance of Hole 75-532. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1 records from A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia. 2726 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 515 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 41 records from Annotated catalogue of the click-beetle tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae). 15 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 35 records from Reptiles Specimens of Akita Prefectural Museum. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 110 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 339 records from UWIZM Snakes. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 395 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 48036 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 19 records from Heinersdorfer Sumpfwiese. 291402 records from ARABEL - Arachnologia Belgica. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 229 records from Nannofossil abundance of Hole 85-573. 10 records from Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea). 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 348 records from Antarctic pycnogonids. 1 records from Seven new species of Night Frogs (Anura, Nyctibatrachidae) from the Western Ghats Biodiversity Hotspot of India, with remarkably high diversity of diminutive forms. 62776 records from MLZ Bird Collection (Arctos). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1444 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 1 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 3 records from Wiese am Waldrand (Gurtweil). 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 859050 records from Queensland Museum provider for OZCAM. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 10 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 54918 records from Herbarium Universitatis Daugavpiliensis. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 51 records from Coccoliths in sediment core GIK23065-3. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 393 records from Dinoflagellate cyst counts on sediment core ABC26. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 19739 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1004 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 6237 records from Plecoptera. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 107 records from Range table from benthic foraminifers in ODP Hole 146-889B. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 16 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 34 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 141 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 2 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 59 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 3 records from Steinbruch Mainz-Weisenau, 3. Jahr. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 2311 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 383 records from Neogene palynomorpha from site 81-552. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 851 records from Pollen profile V and Ausfluss at Krumbach, Germany. 622 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 6 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 203916 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 892 records from (UTC) University of Tennessee Mammals Collection. 21884 records from Birds Specimens. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1952 records from ISM Ichthyology Collection. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 19164 records from DMNS Mammal Collection (Arctos). 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 226 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 2281 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 142891 records from The Himalayan Uplands Plant database (HUP Version 1). 1 records from Artenvielfalt auf dem Schulgelände. 15 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 11 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 31015 records from National Museum of Natural Science. 458 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 37 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 3 records from Renaturierung Werse (Innenbereich Beckum). 356 records from UWYMV Herpetology Collection (Arctos). 54535 records from FUEL - Herbário da Universidade Estadual de Londrina. 292 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 125351 records from Dataflos. 39 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 26 records from Halocosa gen. n., a new genus of Lycosidae (Araneae) from the Palaearctic, with a redescription of H. cereipes (L. Koch, 1878). 175 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 105706 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 80 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 2007 records from Plant specimens of Bihoro Museum. 15 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 7 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 477 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 145 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 1047 records from NZCS Invertebrates New Collection After 1987. 3005 records from Colección Entomológica CDMB. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 16933 records from Lepidoptera (Specimens NRM). 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 2 records from Waidelotinae, a new subfamily of Pyrochroidae (Coleoptera: Tenebrionoidea) from Baltic amber of the Sambian peninsula and the interpretation of Sambian amber stratigraphy, age and location. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2 records from Warnowtal (Rostock). 3272 records from Relative abundance of radiolaria in surface sediments. 1644 records from Las comunidades de myxomicetes de selva baja caducifolia. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 28108 records from Marie-Victorin Herbarium (MT) - Bryophytes. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 27810 records from Collection of saproxylic and xylobiont Beetles. 26 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 27 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 3190 records from Utah State University, Intermountain Herbarium. 14566 records from Canadian Museum of Nature Palynology Collection. 2 records from A new species of Fannia (Diptera, Fanniidae) from Yunnan, China. 946 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 261 records from Planktic foraminifera abundance of Hole 63-469. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 89 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 12 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 96 records from Range table from benthic foraminifers in ODP Hole 172-1060B. 2 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 9902 records from DSMZ Bacteria. 8 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 249174 records from CAS Entomology (ENT). 30 records from Lectotype designations, taxonomic notes and new synonymies in some species of the bee genus Centris Fabricius, 1804 described by Amédée Lepeletier de Saint-Fargeau (Hymenoptera: Apidae). 39614 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 9 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 480 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 550 records from Radiolaria assemblage in sediment core GIK23414-6. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Ctenophora ZMK. 9 records from Studies in Mexican Grasshoppers: A new species of Pedies Saussure (Acrididae: Melanoplinae) with comments on the unusual blue coloration on the abdomens of females and live specimen images for three other congenerics. 92 records from Diversification in the mountains: a generic reappraisal of the Western Ghats endemic gecko genus Dravidogecko Smith, 1933 (Squamata: Gekkonidae) with descriptions of six new species. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 5 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 82 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 562 records from Pollen analysis of sediment core GeoB6518-1. 9 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 108313 records from Arizona State University Hasbrouck Insect Collection. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 2 records from Quarrendorfer Landschaftsschutzgebiet. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 34 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 53 records from Relative abundance of planktic foraminifera in sediment core K11. 7 records from Range table from benthic foraminifers in ODP Hole 139-856C. 10 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 29 records from BMHS Crustacean Collection. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 2812 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 5 records from Loricifera - SMF. 878 records from COA Bird Collection (Arctos). 9 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 22857 records from National Botanic Garden Belgium - Myxomycetes. 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 3 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 196 records from Collection des mammifères d'Auvergne. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 483 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 25 records from Morphologische Daten von Natrix. 7 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 12645 records from Brown University Herbarium. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 1189 records from UWIZM Molluscs. 277 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 5514 records from MCP-Aves - Coleção de Aves. 98 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 265 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 6065 records from LISU Herbario Angola. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 4749 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 628 records from hauterivian_echinoids_of_the_paris_basin. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 218 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 148 records from BioAcoustica: Wildlife Sounds Database. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 197 records from TransForest - vegetation, lichen and fungi data 2016. 8 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 173 records from UWIZM Anoles. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 2451 records from Macrobenthos Chukchi Sea, 1986. 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 3 records from A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species. 42 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 1 records from Protozoa ZMK. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 81 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 170 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 9 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 603 records from Nannofossil abundance of Hole 37-334. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 2 records from Schulgelände SGD/Viersen. 42 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 12859 records from Colecção Entomológica IIA. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 17155 records from MZFC/Coleccion de Aves. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 172 records from Foraminifera abundance of sediment core MD81-LC07. 7123 records from DMNS Egg Collection (Arctos). 9404 records from MZL Invertebrate Collections. 1303 records from Crustacean specimens of Bihoro Museum. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 17 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 17114 records from Collection of Coleoptera. 2 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 5408 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 1726 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 3 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 17 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 831 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 354 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 142 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 3800 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 4751 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 14 records from A reappraisal of the California Roach / Hitch (Cypriniformes, Cyprinidae, Hesperoleucus / Lavinia) species complex. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 11 records from Gewann Krampf (Heilbronn). 116461 records from Naturalis Biodiversity Center (NL) - Crustacea. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 421 records from Pollen profile from Muscotah Marsh B. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 4 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 3340 records from Palaeobiology collection, FAU Erlangen. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 8 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 1 records from Hemichordata collection of National Museum of Nature and Science. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 3537 records from ATCC Bacteria Collection Catalog. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 2044 records from The Broward College Insect Collection. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from Description of Harpactea popovi sp. n. from Bulgaria with further taxonomic notes on related species (Araneae, Dysderidae). 24283 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 7446 records from Fish specimens of Toyama Science Museum. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 5 records from Anderemaeus (Acari, Oribatida) - overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 6004 records from Colección Limnológica Universidad de Antioquia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 2 records from Wald am Schloss Wittgenstein Bad Laasphe. 659 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 139383 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 181857 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 3 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 41 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 3 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 27108 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 1825 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 351 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 4 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 2 records from Amtsrain Apolda-Zottelstedt. 22 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 3 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 8 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 3 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 146 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle RNC:102. 304 records from Inventario de macroalgas de Isla Guadalupe, México. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 52 records from Range table from planktonic foraminifers in ODP Hole 167-1010E. 10 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 9135 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 115 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 29876 records from European Moth Nights. 2 records from Genetic evidence supports Sylvilagus mansuetus (Lagomorpha: Leporidae) as a subspecies of S. bachmani. 5515 records from Colección de Anfibios. 4 records from Seodaemun Museum of Natural History Fossil. 11143 records from NBMB Herps. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 24795 records from Université d'Aix-Marseille. 386 records from Foraminifera distribution of sediment core KS310. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 24 records from Aves de Caño Cristales, La Macarena, Meta. 13 records from A supplement of the genus Homogryllacris Liu, 2007 (Orthoptera: Gryllacrididae Gryllacridinae) from China. 4 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 3 records from Umgebung der Gesamtschule Hamburg-Winterhude. 138 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 12 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 3187 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 70 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 1784 records from Distribution of planktic foraminifera of sediment core M33/1_SL_NAST. 5 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 568 records from Expedición Providencia I - INVEMAR. 1 records from Contribution to the tribe Pentoffiini (Cicadellidae: Evacanthinae) with descriptions of two new species and the male of Evanirvana aurea Hill, 1973. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 211452 records from University of Michigan Museum of Zoology, Division of Birds. 7 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 2406 records from UWYMV Bird Collection (Arctos). 11994 records from Hatikka Observation Database. 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 200187 records from inatura - Erlebnis Naturschau Dornbirn. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 386 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 11 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 1000 records from Collection Graptolithina fossil SMF. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 11 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 82649 records from Specimen Database of Colorado Vascular Plants. 25953 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 12 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 171 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 15 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11584 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 2 records from An XXL-CT-scan of an XXL Tyrannosaurus rex skull. 6 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 107580 records from Database of invertebrates collected in Mongolia. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 34 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 1112 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 61999 records from La familia Asteraceae en México. Fase VI. 610 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 607 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 213 records from Pollen record of profile 3TZ. 825 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2312 records from Mycological collection of the National Museum. 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 6 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 352976 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 100 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 10160 records from UAM Fish Collection (Arctos). 1165 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 8808 records from Survey of bumblebees in central Alberta - 2018. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 70 records from Isotope tracer experiment: meiofauna counts. 26841 records from MSUM Ichthyology and Herpetology Collections. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 3171 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 5 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 31 records from Nannofossil abundance of Hole 94-611E. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 126 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 3 records from Selztal bei Friesenheim. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 18452 records from UCM Mammal Collection (Arctos). 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 184807 records from Tiroler Landesmuseum Ferdinandeum. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 271952 records from Natural History Museum, Vienna - Herbarium W. 78 records from Mammals (GNHM-MM). 3 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 3 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 63293 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 2255 records from (Appendix B) Benthic foraminifera extinction group species in combined DSDP Hole 33-317B and sediment core KR9912-PC4. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 40 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 22 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 248439 records from Arizona State University Vascular Plant Herbarium. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 3 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 1900 records from Fungi Collection. 6 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Thirteen new records of ferns from Brazil. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 679 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202392 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 4 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 1 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40281 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 26 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 3 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 4 records from Deponie Klausdorf. 2 records from Schulgelände (Wetter). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 6 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 3 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 61 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 8096 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 14 records from Erlengraben/Lipp-Tal (Östringen). 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 725 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 3447 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 1872 records from Herbier National de Guinée (HNG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 61 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 4 records from NZCS Paloemeu River - Grensgebergte Mountains Expedition Conservation International RAP 2012. 6071 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 24 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2548 records from BioGIS - Reptiles - HUJ collections. 5 records from An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters. 78 records from Nannofossil abundance of Hole 27-259. 179 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 2 records from AKG-Gelände (Bensheim). 12 records from Newly recorded leafhoppers of the subfamily Cicadellinae (Hemiptera: Cicadellidae) with description of a new species from Pakistan. 54 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 1597 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 6 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 226 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 8 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 118 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 20 records from A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa. 1271 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 58 records from Сypripedium guttatum Sw. in the Komi republic. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from Nannofossil abundance of Hole 73-521A. 31 records from Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 773 records from NSW South Coast & ACT plants. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 8 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 79 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 9 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 5361 records from Colección Ornitológica de la Universidad del Valle. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 77 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 7 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 324 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 6 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 19 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 7 records from Deep-sea ascidians from Papua New Guinea. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 159 records from Nannofossil abundance of Hole 67-499B. 77 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 463 records from Foraminifera abundance of sediment core IN68-9. 475044 records from NatureServe Network Species Occurrence Data. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 7873 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 881 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 4 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 67 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 2 records from Naturgrundstück (Eutin). 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 68 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 8 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 2 records from Truppenübungsplatz Panzerkaserne Böblingen. 80 records from The Calliphoridae (Diptera) of Armenia. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 14 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 29 records from Herbarium Senckenbergianum (FR) - Protista. 3 records from Zoology in the Middle East. 2867 records from Pollichia Pilzherbar. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 756 records from Neogene palynomorpha from site 93-603, part 2. 14 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 7 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 5 records from On the types species of the New World dung beetle genus Canthidium Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae), with an annotated checklist of species. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 26 records from Orthoptera (Tettigoniidae and Acridoidea) from Miombo woodlands of Central Tanzania with the description of new taxa. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 238 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 218 records from Nannofossil abundance of Hole 49-408. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 20 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 286525 records from Allan Herbarium (CHR). 254268 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 1510 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 9810 records from Royal British Columbia Museum Entomology Collection. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 122 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 607514 records from Plant. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 44 records from Planktic foraminifera abundance of Hole 63-472. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 72399 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 394 records from Reptilia ZMK. 85277 records from University of Ghana - Ghana Herbarium. 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 143 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1911 records from Pollen profile RAC20, Lake Racou, France. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 7 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 10898 records from Inventario de Hymenóptera; parasítica en México. 2 records from VSN-Wiese. 3 records from Fourth note on the Dinosauria of the Laramie.. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 35 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 23 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 22516 records from MfN - Fossil Fish Collection. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 7462 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 924 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 32 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 23 records from Nannofossil abundance of Hole 24-233A. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 5 records from Intertidal Euryleptid polyclads and description of a new Stylostomum Lang, 1884 from Maharashtra, India. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 104 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 312 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 3712 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 817 records from Lucanidae. 4579 records from Estación Biológica de Doñana - CSIC, Anfibios. 34103 records from R. L. McGregor Herbarium Lichen Collection. 472 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 21 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1 records from Two new species of obligatory termitophilous rove beetles from Brazil (Coleoptera: Staphylinidae: Termitomorpha Wasmann). 51637 records from SIO Benthic Invertebrate Collection. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 203 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 490 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 7 records from Collection Malakologie - SMNG. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 86 records from UWIZM Cnidarians. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 2 records from New Cretaceous soldier beetle (Cantharidae) from Burmese amber with preserved coloration on the elytra. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 440 records from Antarctic and Subantarctic Asteroid zoogeography. 5 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 61 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 50 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 7 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 63539 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2648 records from University of Sindh Jamshoro Herbarium. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 2 records from MFS-Plantulas - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Plântulas. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 4 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 1 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 41 records from Registros Primates Neotropicales Convocatoria APC. 41 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 134 records from Pollen record of profile 3TZ2. 1000 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 94 records from A new species of the Liolaemus alticolor - bibronii group (Iguania: Liolaemidae) from East-central Argentina. 314 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 190 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 2 records from Opsarius putaoensis, a new species of subfamily Danioninae (Actinopterygii, Cyprinidae) from the Irrawaddy River basin in northern Myanmar. 85924 records from Collection Aves (bird skins) SMF. 92 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 1928 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 1 records from Nymph inadvertently described as new species for a fourth time? On the identity of Euscelimena hardi (Tetrigidae: Scelimeninae) with general remarks on the identification of pygmy grasshopper nymphs. 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 15968 records from JOI - Herbário Joinvillea. 4 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 67 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 3 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 31 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 6 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 12 records from A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan. 33 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 2020 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 5 records from Notes on the grasshopper genera Longgenacris You & Li, 1983 and Fruhstorferiola Willemse, 1922 (Orthoptera: Acrididae: Melanoplinae) with proposal of a new synonym. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 1365 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 1 records from Zetes pallidulus. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 72 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 754 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 3 records from Visual Plants (144.41.33.158) - Private collection of Barbara Kueppers. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 14 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Freiheitsring (Frechen). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 4400 records from USAC Mammals Collection. 5 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 2 records from Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 5 records from On some species of the genus Acrolocha Thomson, 1858 of the Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1197 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 10 records from REVISÃO DO GÊNERO “ LEPTOCYSTA ” STAL (Hemiptera, Tingidae). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 20941 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1191 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 1 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 1 records from A new genus and species of burrower bugs (Heteroptera: Cydnidae) from the mid-Cretaceous Burmese amber. 8069 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 15757 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 11877 records from Formidabel; Belgian Ants Database. 2568 records from Fish (NHMK-PI). 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 92 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 51 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 216 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 4 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 1 records from A new African Apiocera species (Apioceridae, Diptera). 164923 records from CAS Invertebrate Zoology (IZ). 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 93 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 46 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 830 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 52211 records from MCP - Coleção de Abelhas. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 2 records from Charinus rocamadre (Amblypygi, Charinidae): description of the female, ultrastructure of the male and female gonopods, and mitochondrial DNA sequences. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 45 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 2 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 18224 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 22 records from Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration. 437 records from Bird specimens of Bihoro Museum. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 985 records from Freshwater Fishes of Bulgaria. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 5 records from On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae). 16 records from Taxonomic review of the genus Wasmannia.. 197 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 2 records from A new genus of cricket with one new species from western Yunnan, China (Orthoptera: Gryllidae: Gryllinae). 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 2 records from Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features. 3 records from A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador. 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 1 records from New genera and species from the Belly River Series (mid-Cretaceous). 7 records from Revision of Sinonereis Wu & Sun, 1979 (Annelida: Nereididae). 12 records from A revision of the Costa Rican species of Stenoeurilla Brailovsky & Barrera (Hemiptera: Heteroptera: Coreidae: Stenoscelideini), with the description of two new species, new distributional records, synonymical note, and key to the known species. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 120 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 36 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 5776 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1142431 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 13945 records from MfN - Fossil plants (Paleophytic). 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 5255 records from Ibaraki Nature Museum, Fish collection. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 3 records from A new genus and new species of Potamidea (Crustacea: Decapoda: Brachyura: Potamoidae), the first stygomorphic cave crab known from China and East Asia. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 6 records from New records of two endemic troglobitic and threatened arachnids (Amblypygi and Opiliones) from limestone caves of Minas Gerais state, southeast Brazil. 61942 records from EAC - Herbário Prisco Bezerra. 29105 records from Marine Biological Sample Database, JAMSTEC. 91 records from CNIN/Tipos Homoptera. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 88391 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 18 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 3 records from Tobrilus saprophagus sp. n. and Epitobrilus interstitialis sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 30260 records from Collection Crustacea - ZMB. 66 records from Range table from ostracoda in ODP Hole 151-910D. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 36 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 11 records from Fatkullina imitata n. sp., second species of a unique cheilostome bryozoan genus with reversed-polarity zooidal budding, and new family Fatkullinidae. 74 records from Nannofossil abundance of Hole 24-233. 1464 records from CNIN/Tipos Coleoptera. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 82 records from A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1399 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 154 records from Dermaptera in the icipe collection. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 25 records from Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico. 292 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 59976 records from Naturalis Biodiversity Center (NL) - Mammalia. 423 records from Nannofossil abundance of Hole 74-525A. 2082 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 7 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1098 records from What bug is that. 3803 records from Ghent university - Zoology Museum - Nematod Collection. 54 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 4 records from Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 108 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 6506 records from Cal State LA Herbarium. 19 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 316 records from Nannofossil abundance of Hole 49-410. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1 records from Solving a long-standing nomenclatorial controversy: designation of a neotype for the southern sea lion Otaria flavescens (Shaw, 1800). 3 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 42 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 38841 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 319 records from Pollen data of trap CB4. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 14 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 1 records from Nothrus bicarinatus. 10 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 200 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 4 records from Draubiotop Lavamünd. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 285 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 164 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 8328 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 6859 records from Plan de vertebrados de la Patagonia. 25 records from Fleas (Siphonaptera) of Turkey: species composition, geographical distribution and host associations. 7 records from A revision of the genus Petta Malmgren, 1866 (Annelida: Pectinariidae), with two new species from deep waters of southeastern Australia, and comments on phylogeny of the family. 6 records from Revised status of Oridryas Meyrick, 1938: new synonyms of Ypsolopha Latreille, 1796, and Ypsolopha parenthesella (Linnaeus, 1761) (Yponomeutoidea: Ypsolophidae). 190 records from Nannofossil abundance of Hole 67-499. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40344 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 212 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 66 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 3 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 6 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 28 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 6 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1 records from Description of females of Chilarboreus Ruta, 2011 (Coleoptera: Scirtidae: Scirtinae). 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 401 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 242 records from UTEP Fish (Arctos). 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 8 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 1400 records from AlgaTerra. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 117 records from Distribution of planktonic foraminifera of sediment core SH1972_7. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 65 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 4 records from Danielsberg (Mölltal, Kärnten). 7346 records from MfN - Fossil vertebrates III. 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 60 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 8633 records from HSU Vertebrate Museum Mammals Collection. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from Landschaftspflegehof (Berlin). 1 records from Bachpatenschaft Beeke. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 2 records from Revision of the Scopula dubernardi species group: how many species? (Lepidoptera: Geometridae, Sterrhinae). 16 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 5224 records from Insect specimens of Omogo Mountain Museum. 537 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 1402 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 41 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 368 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 694 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 59469 records from Canadian Museum of Nature Mammal Collection. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 277522 records from Biodiversitätsdatenbank des Landes Salzburg. 17713 records from NCSM Mammals Collection. 17 records from Nannofossil abundance of Hole 52-418. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 12 records from Les occurrences des Gymnospermes de l'herbier du Centre National de Floristique (Côte d'Ivoire). 16 records from Mesozooplankton - Crustacea from the South Adriatic Sea. 27 records from Peripus, a new genus of Xanthopygina (Coleoptera: Staphylinidae) from South America. 28 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 747 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 1 records from On the Chilopoda from Turkey. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 2 records from Planktic foraminifera counts of multinet PS2616-5. 4207 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 151 records from CHAS Botany Collection (Arctos). 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) — three possibly threatened Brazilian species. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 3 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 6393 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102476 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 10212 records from Spider (NSMK-SP). 27947 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 10650 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 77414 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 302 records from Malawi-Cicindelidae-Biodiversity-Data. 18058 records from Fish Collection of Yokosuka City Museum. 4 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 4507 records from ARC-PPRI: National Collection of Insects: Coleoptera Collection (1879-2012). 38 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 46118 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 1 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1 records from Lacunicambarus dalyae: a new species of burrowing crayfish (Decapoda Cambaridae) from the southeastern United States. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 287 records from Nannofossil abundance of Hole 66-488. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 85 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 26918 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 9304 records from Echinoderm collection of National Museum of Nature and Science. 3 records from Wirbach-Taubental (Bad Blankenburg). 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 180988 records from LSUMZ Birds Collection. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 28 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 20995 records from Auburn University Museum of Natural History Mollusks. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 13 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 54 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 41 records from New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae). 3512 records from Wikiplantbase #Sicilia. 1153 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 284 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 21 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 48 records from Foraminifera and stable isotopes of sediment core PS2076-1. 2504 records from Database of Australasian Vertebrate Occurrences. 289 records from bmhs_butterfly_collection. 498 records from Bekkelag basin, Inner Oslofjord. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 1 records from Nottekanal, Klasse 7 - 10. 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 311 records from Nannofossil abundance of Hole 37-333. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 897332 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2740 records from Fungi specimens of Saitama Museum of Natural History. 1530 records from Pollen record of sediment core Bokanjacko Blato 1. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 46680 records from Bosque Mesófilo de Montaña de México. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 120410 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 27578 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 406575 records from Herbarium of Taiwan Forestry Research Institute. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 3 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25374 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 1078 records from Pollen profile from Seminary School Basin. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from Oribates calcaratus. 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 490387 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 5335 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 27 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 47 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 135159 records from BioFokus. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2443 records from Cnidaria MZS. 3464 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 4 records from New Prionospio and Laubieriellus (Annelida: Spionidae) species from Southeastern Brazil. 6 records from Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae). 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 348 records from Foraminifera abundance of Hole 57-440B. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 6 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 8458 records from UTEP Insects (Arctos). 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 27 records from A new genus and two new species in the tribe Selizini (Hemiptera: Fulgoromorpha: Flatidae) with a checklist for the tribe from China. 127 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ulf Soltau. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 15 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28439 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 61324 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 909 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 8980 records from MEXU/Tipos de plantas vasculares. 98 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 8551 records from Insect (ENHM-IN). 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 12 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 346 records from Packer Collection /Madagascar. 18 records from Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 262 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 907 records from Pollen profile Märchenwald B, Harz, Germany. 61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 13940 records from The Vascular Plants Collection of the University of Goettingen. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 59 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 13 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 13269 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 94061 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 7 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America
Keywords: GBIF; biodiversity; species occurrences